The JSE/BESA merger : navigating the integration minefield - Bowen, Amanda (SAGE knowledge. Cases., 2016)
A few days before the JSE Limited (JSE) and the Bond Exchange of South Africa Limited (BESA) merged in June 2009, Nicky Newton-King, deputy CEO of the JSE - who had been tasked with leading the integration of the two organisations - reviewed what she had done so far and the plans she had put in place to ensure a smooth integration. A great deal of time and work had been invested in planning and organising the merger, and she did not want a misstep in the integration process to derail the entire merger. She wondered if she had done enough to ensure a smooth integration.